Levels of Porphyromonas gingivalis Fimbriae and Inflammatory Cytokines in Gingival Crevicular Fluid from Adult Human Subjects - Hirose, Kimiharu; Isogai, Emiko; Miura, Hiroko; Ueda, Itsuo (MICROBIOLOGY and IMMUNOLOGY, 1997)
The Porphyromonas gingivalis fimbriae level was examined in the gingival crevicular fluid (GCF) from adult human subjects using an immunoblot assay with a monoclonal antibody. The cytokines, interleukin-1α (IL-1α), IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) levels in the GCF were quantified by enzyme-linked immunosorbent assay (ELISA). The reactivity of the GCF samples with the monoclonal antibody against P. gingivalis fimbriae was related to the IL-1β, IL-6 and TNF-α levels. Moreover, the fimbriae content was associated with the gingival index (GI). In contrast, no significant correlation was seen between the fimbriae content and IL-1α level. These results suggest that there are possible associations between P. gingivalis fimbriae and IL-1β, IL-6 and TNF-α in the gingival crevicular fluid.